Pemberdayaan Masyarakat Melalui Program Ketahanan Pangan Dalam Pembangunan Desa - Amboisa, Nadia Fransiska; Pradita, Antonia Eka; Iku, Agustina Bete; Pratiwi, Angelika Yuni (Journal of Community Service and Society Empowerment, 2024)
The main focus of this research is community empowerment in Tiong Keranjik Village, Belimbing Hulu subdistrict, Melawi district, West Kalimantan through the food security program. The aim of this research is to analyze the impact and success factors of the community empowerment program in the context of the development of the Tiong Keranjik village. The research method used included document analysis to obtain a comprehensive picture of the implementation of community development programs through empowerment. This research shows that making village communities independent (empowered) through food security programs has a very positive impact. With adequate resources, and better market access, local farmers can increase their productivity and income. Apart from that, the action program also strengthens human capacity to utilize natural products continuously by emphasizing environmentally friendly agricultural practices. However, the study identified several challenges facing local farmers, such as climate change, which can affect crop yields and market fluctuations. In addition, local social and economic factors influence the sustainability of empowerment programs. Therefore, it is recommended to improve coordination between institutions, strengthen support policies and actively involve the community in design and decision-making activities. This research makes a significant contribution to our understanding of village community empowerment in the context of Tiong Keranjik village, Melawi district. It is hoped that the policy implications of this research can help design more sustainable empowerment strategies, especially to increase community food security against external and internal challenges in the development of Tiong Keranjik village, West Kalimantan.